2012
DOI: 10.1007/s10661-012-2552-x
|View full text |Cite
|
Sign up to set email alerts
|

A phytoremediation approach using Calamagrostis ligulata and Juncus imbricatus in Andean wetlands of Peru

Abstract: Emergent plant species growing in Andean natural wetlands have shown efficient phytoremediation capabilities in wetlands polluted by acid mine drainage. However, the types and amounts of heavy metals accumulated by native plant species are not well understood. In this study, we focused on determining heavy metal concentrations and bioaccumulation factors in Calamagrostis ligulata and Juncus imbricatus. Two acid wetlands located above 3,500 m a.s.l. in Ancash, Peru were assessed. Physico-chemical parameters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Similar percentages of Zn removal were also observed when A. pinnata and L. minor were used (Vaseem and Banerjee, 2012). Other plant species such as T. latifolia (Sasmaz et al, 2008), C. ligulata, J. imbricatus (Miguel et al, 2013), E. acicularis (Ha et al, 2009), P. cummunis, T. angustifolia, C. esculentus (Chandra andYadav, 2011) and P. stratiotes (Lu et al, 2011) have shown potential to remediate Zn-contaminated waters.…”
Section: Phytoremediation Of Zn-contaminated Sitesmentioning
confidence: 55%
“…Similar percentages of Zn removal were also observed when A. pinnata and L. minor were used (Vaseem and Banerjee, 2012). Other plant species such as T. latifolia (Sasmaz et al, 2008), C. ligulata, J. imbricatus (Miguel et al, 2013), E. acicularis (Ha et al, 2009), P. cummunis, T. angustifolia, C. esculentus (Chandra andYadav, 2011) and P. stratiotes (Lu et al, 2011) have shown potential to remediate Zn-contaminated waters.…”
Section: Phytoremediation Of Zn-contaminated Sitesmentioning
confidence: 55%
“…Research conducted by many authors revealed that some plant species, owing to their specific features, have the ability to absorb and degrade xenobiotics polluting the environment through their active impact on physical, chemical and biological processes occurring in nature, changing them to enable their own life cycle to take place. Moreover, these plants possess defense mechanisms, absorbing, metabolizing and/or concentrating toxic substances in their own tissues and in this way cleaning the environment (Padmavathiamma and Li 2007;Ramamurthy and Memarian 2012;Miguel et al 2013). A toxic effect of nickel on plants observed in the presented investigations was visible as leaf chloroses, deformation of the aboveground parts and roots.…”
Section: Discussionmentioning
confidence: 99%
“…These wetlands act as buffers to seasonal dry conditions and contamination by, e.g., heavy metals, thus securing water quantity and quality. [87][88][89] Peat bogs are highly susceptible to climate change and other anthropogenic impacts. Changes in climatic patterns combined with glacier shrinkage and, e.g., mining and Land Use and Land Cover Change (LULCC) activities could severely alter and fragment these fragile ecosystems thus affecting long-term water storage.…”
Section: High-andean Lakes and Wetlandsmentioning
confidence: 99%